Oʻahu - Peebles, Douglas (Mutual Publishing, 2001)
Many people think of Oahu and remember the small parts they know best. A particular beach. A favorite restaurant. A hotel pool or a mountain pool. The feeling of standing at the USS Arizona Memorial. The view over the Pali Lookout. In this volume, the many parts of the island, the remarkable range of views, are brought together in one place. Readers can compare the windward beaches with those on the leeward side, can inspect the mountainsides and the broad valleys, and in many cases can see things none but the most experienced islander ever sees.